Prevalence of Malocclusion in 6 and 12 Year-old Schoolchildren from Choshuenco – Neltume, Chile (International Journal of Medical and Surgical Sciences, 2016)
To develop preventive and interceptive strategies in orthodontics is necessary to know the prevalence of malocclusion of the population in which is intended to introduce these measures. The aim of this study was to determine the prevalence of malocclusion in schoolchildren of 6 and 12 year-old from Choshuenco and Neltume 2015, belonging to the commune of Panguipulli, Chile. A descriptive study of census was conducted. The total sample was 91 children and adolescents enrolled in educational institutions in the towns of Choshuenco and Neltume. A visual clinical examination was performed to determine the number of individual malocclusions according to the method of Bjork et al. (1964). For data analysis descriptive statistic was performed using Excel program. Prevalence of malocclusions was 60 % at 6 years and 91.3 % at 12 years. Prevalence data exceed those reported nationwide so it is necessary to reinforce promotional measures in the population and promote preventive - interceptive actions taking place in these locations.
Keywords: Prevalence; Malocclusion; Chile